A statistical quality control study on Selecta Wall's, Incorporated - Abarquez, Joselito; Esguerra, Kathryn; Inumerable, Jennifer (Diliman, Quezon City College of Engineering, 2003)
A study was made on the production and quality system of Selecta Wall's, Inc., one of the leading ice cream manufacturers in the country. The study was conducted during June to September of 2002. The group identified the Double Dutch variant in the bulk ice cream line as the particular product to be studied because it had the highest sales volume among the 58 variants of the bulk ice cream line. The problem areas were identified using Pareto Analysis and Process Failure Mode Effects Analysis (PFMECA). The group identified microbial contamination, sensory defects and fill weight variation as the major quality concerns. Ishikawa diagrams were constructed to identify the causes of the mentioned problems. The group used the data provided by the company to construct the attribute control charts and variable control charts for the ageing and filling process and to identify the assignable causes of variation. The processes were determined to be out of control because of several points lying outside the control limits. For the ageing process, the incorrect level of refrigerant was the assignable cause. For the filling weight variation, it was identified that the variation in ambient air conditions, which affects the amount of overrun in the ice cream, as the assignable cause. Lastly, for the sensory defects, it was identified that the clogging of the fruit feeder was the assignable cause. After setting up the revised control charts, the process capability was determined. The ageing process was found to be capable because it has a 3.975 capability index. On the other hand, the filling Process was found to be incapable because of the 0.526 and 0.238 values of the capability indices for the one gallon and half gallon, respectively. The fruit feeding process has an index 0.711, rendering it incapable. The group recommends that the company conduct a design of experiments and a statistical process control (SPC)with the help of a Quality Improvement Team (QIT) to determine the appropriate refrigerant level and the parameters of ambient air that affects the amount of overrun. The SPC will be performed through the use of its seven tools, which includes the histogram, check sheet, Pareto chart, Ishikawa diagram, defect concentration diagram, scatter diagram, and control charts. It was also recommended that the inclusions be dumped in smaller batches to prevent the clogging of the fruit feeder. The study can also be extended to other ice cream flavors and to the Impulse ice cream division to further improve the company's quality level. Statistical Process Control should likewise be applied to other stages of ice cream production.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Selecta Wall's, Incorporated; Ice cream industry; Quality control